Atomic reconstruction and oxygen adsorption behavior of the pyrite (100) surface: a DFT study. Issue 12 (14th March 2023) - Chen, Manjiao; Hu, Xinjun; Zhou, Xinjun; Li, Xiulan; Tian, Jianping
Abstract : S n and –[Fe–S] n – structures will form on the reconstructed surface of FeS2, and the binding energy of S n to the matrix is lower than that of –[Fe–S] n –. The cohesive energy of S n is higher than that of –[Fe–S] n –, so the –[Fe–S] n – structure is more easily oxidized than S n . Abstract : The analysis of the surface chemical behavior of pyrite is highly crucial in the fields of environmental conservation, metal extraction, and flotation separation. In this paper, the mechanism of atomic reconstruction on the pyrite surface and the adsorption behavior of O2 on a reconstructed surface are calculated by density functional theory (DFT). Different reconstruction surfaces were constructed by deleting S and Fe atoms on the (100) surface of pyrite. In addition, the geometric configuration, formation energy, binding energy, cohesion energy, and surface electronic properties of the reconstruction surface were calculated. The adsorption energies and geometric configurations of O2 on different reconstructed surfaces were also determined. The results show that under Fe-poor conditions, the charge of Fe atoms increases, and S atoms form S n on the reconstructed surface. The binding energy between the S n and the substrate (ideal surface) is lower, which is similar to the S n adsorption on the substrate surface with the Fe atom as the site. S n has high cohesive energy and is resistant to being attacked by oxidants, which leads to structural collapse, and a low affinity for O2 . Under S-poor conditions, the –[Fe–S] n – plane structure formed on the reconstructed surface. The –[Fe–S] n – structure stably bonds to the substrate by an Fe–S bond, and exhibits strong binding energy. However, the –[Fe–S] n – structure has low cohesive energy and exhibits thermodynamic instability. In contrast, O2 shows a strong affinity for the –[Fe–S] n – structure, indicating that the deficiency of the S atom promotes the surface oxidation reaction. The mechanism of atomic reconstruction on the surface of pyrite is of utmost importance for understanding its surface chemical behavior.